Geomagnetic Effects in Spatial Distributions of Particle Precipitation in Terms of Particle Energy Channels. Issue 9 (8th September 2020) - Shen, Han‐Wen; Shue, Jih‐Hong; Dombeck, John; Li, Hsien‐Ming
Abstract: This study examines the spatial distributions of precipitation during active and quiet times. Most previous studies commonly classified precipitation into different energy spectral types, but we utilized a classification according to particle energy channels. A general conclusion derived from these distributions suggests that regardless of active and quiet times, low‐energy (<1 keV) and high‐energy precipitating particles are mostly on the dayside and nightside, respectively. A comparison with past results reveals that the high‐energy electron precipitation during quiet times is mostly due to wave scattering and that during active times is mainly produced by quasi‐static potential structures (QSPS) and Alfvénic acceleration, while low‐energy electron precipitation is mostly caused by QSPS and Alfvénic acceleration regardless of quiet and active times. For both high‐energy proton and electron precipitation, the nightside dawn‐dusk asymmetry of their distributions during active times is found to be opposite of that during quiet times. We infer that the distribution of high‐energy precipitation during quiet times is dominated by the curvature and gradient drifts, while during active times it is mainly due to the physical processes or phenomena related to substorms in the magnetotail. Empirical orthogonal function analysis has been applied in this study to derive where the flux has the maximum enhancement as the geomagnetic activity increases. The results further demonstrate that low‐energy and high‐energy protons mainly increase in the noon and postmidnight sectors, respectively. The highest enhancements of low‐energy and high‐energy electrons are in the prenoon and premidnight sectors, respectively. Plain Language Summary: The dynamic nature of the magnetosphere can precipitate charged particles into the upper atmosphere in the high‐latitude region, creating spectacular auroras. The number and energy fluxes of these particles and their distributions vary with the geomagnetic activity. When people studied particle precipitation, they usually categorized the precipitation according to the monoenergetic, broadband, and diffuse features shown in energy spectra. Using new categorization criteria based on different energy channels, we can conclude that, in general, low‐energy channels (154–224 and 688–1, 000 eV) are mostly distributed on the dayside, while high‐energy channels (2, 115–3, 075 and 6, 503–9, 457 eV) are mainly distributed on the nightside regardless of geomagnetic conditions and particle charge types. Our results also demonstrate an intriguing dawn‐dusk asymmetric distribution of high‐energy protons/electrons on the nightside in reference to the magnetospheric state. High‐energy precipitating protons and electrons are respectively on premidnight and postmidnight during quiet times because of the regular drift motion of the magnetospheric particles, but their distributions during active times are swapped due to the physical processes of substorms in the magnetotail. All the results derived from this study provide a new look at particle precipitation, which can help reveal the secret of the dynamic magnetosphere. Key Points: A new method of categorizing particle precipitation using energy channels is implemented Low‐energy (high‐energy) precipitation is, in general, mostly on the dayside (nightside) regardless of geomagnetic states The dawn‐dusk asymmetric distribution of high‐energy protons/electrons during quiet times is the opposite of that during active times